Politik Kesejahteraan Sosial dan Pemberdayaan Masyarakat: Kasus Ketergantungan Kebijakan Bantuan Sosial di Temanggung, Jawa Tengah - Nursari Sugiastuti; Roma Ulinnuha (Universitas Sebelas Maret, 2023)
One of the government's strategies for overcoming poverty is to reduce the burden of public expenditure, which is realized in the form of social assistance. The government's social welfare policy in the form of social assistance is something that is truly phenomenal and is always eagerly awaited by the recipients. One of the effects is to provide a sense of security and feel like you are in a comfort zone, in other words, dependence on social assistance. But there are beneficiaries who are dissatisfied with their situation, they want positive changes and not to be recipients of social assistance forever. They made conscious changes by empowering their group of fellow recipients of the Family Hope Program's social assistance. This research is field research in the form of a case study located in Temanggung Regency with the research object being a Joint Business Group which carries out the establishment and initial capital independently, namely from the results of setting aside some of the social assistance money they receive. The research method used is a qualitative descriptive method, while data is obtained from observations, interviews and documentation studies from related sources. This article tries to review the theme with Anthony Giddens' structuration theory, which states that all social action requires agents and structures where agents and structures cannot be separated from each other because they are dual. This also happens to Joint Business Groups as agents and government policies as structures, both of which are interrelated and influence each other.